2016
DOI: 10.1149/07509.0025ecst
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Thick Metal Ohmic Contact Fabrication Using Surface Activated Bonding

Abstract: junctions by surface activated bonding (SAB). The effects of the annealing temperature process on the electrical properties of the junctions were investigated by measuring their current voltage (I-V) characteristics. It was found that the leakage current of the reverse bias of n-Si/Al junctions was improved and the I-V characteristics of p-Si/Al revealed excellent linearity properties after the junctions annealing at 400 °C. The interface resistance of p +-Si/Al, and n +-Si/Al junctions decreased with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…The FAB irradiation conditions in preparing Junctions (A) and (C) were similar to those in our previous work. 23) The schematic cross sections of the respective junctions are shown in Fig. 1.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FAB irradiation conditions in preparing Junctions (A) and (C) were similar to those in our previous work. 23) The schematic cross sections of the respective junctions are shown in Fig. 1.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…On the assumption that ultrathick metal junctions on semiconductors could provide a solution for this problem, we previously fabricated Al foil=Si junctions by SAB and examined their possibility as contacts and interconnects. 23) We have recently found that Al foils bonded on n-4H-SiC layers worked as Schottky contacts. 24) In this paper, we examine the electrical properties of Al foil= 4H-SiC junctions in comparison with Schottky junctions fabricated by evaporating Al films with the emphasis on the effects of annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Si/ Si 接合 7,9 11) , Si / InP 接合 12) , Si/ GaAs 接合 13,14) , Si/ InGaP 接合 15) 等の同種・異種半導体の貼り合せ,Al/Si 接 合 16,17) 等の金属(箔)と半導体の貼り合せ,Cu/Au 接合 18) 等の金属同士の貼り合せが実現され,化合物半導体多接合太 陽電池 19…”
Section: の貼り合せが可能であること,という特徴がある.これまで,unclassified
“…We previously successfully fabricated Al/p-Si junctions by SAB and found that the current-voltage (I-V) characteristics of the bonded junctions revealed Schottky rectifying property. 7,8 The formation of ohmic contact generally requires a heat-treatment process so that the evaporated metals could react with the semiconductor to reduce the barrier height of the interface. Thus, to investigate the annealing temperature dependence of the electrical properties of the bonded Al/Si junctions is very necessary to realize the fabrication of the thick film metal electrode.…”
mentioning
confidence: 99%